Impact of social capital and clinical factors on the oral health-related quality of life of vulnerable children and their families (Bioscience Journal, 2025)
This study assessed the impact of individual social capital and clinical variables on the oral health-related quality of life (OHRQoL) of vulnerable children and their families. This cross-sectional observational study included children of both sexes and their parents or guardians. The OHRQoL was assessed using the Brazilian version of the ECOHIS questionnaire. Individual social capital was evaluated through participation in community, school, and religious activities. The criteria recommended by the WHO were used to analyze dental caries and malocclusion. Adjusted logistic regression models estimated the odds ratios at a 95% CI; the multiple regression model included variables with p < 0.20 in the individual analyses, and those with p ≤ 0.05 remained in the final model. Younger children with caries occurrence and lower social capital are 1.74 (95% CI: 1.13-2.68), 2.89 (95% CI: 1.88-4.45), and 3.69 (95% CI: 2.36-5.78) times more likely to experience a higher impact on OHRQoL (p < 0.05). Families of children with caries occurrence and lower social capital are 2.31 (95% CI: 1.52-3.50) and 3.56 (95% CI: 2.29-5.54) times more likely to experience a higher impact on OHRQoL (p < 0.05). Families of children with caries experience and lower social capital are 2.11 (95% CI: 1.40-3.19) and 3.55 (95% CI: 2.89-5.50) times more likely to show a higher impact on total OHRQoL (p < 0.05). Dental caries experience and lower individual social capital were associated with a higher impairment of the OHRQoL of children and their families in conditions of social vulnerability.